Loss, Doubt, and Betrayal: Strands of Vaccination Skepticism on Three Facebook Pages Involved in the Controversy Over Human Papillomavirus (HPV) Vaccination - Agergaard, Torben Esbo; Nielsen, Kristian H. (Frontiers in Communication, 2020)
We conducted a discourse analysis of posts, comments, and contextual material on three Danish Facebook Pages, all established as a consequence of social groups’ skepticism to HPV vaccination. We accessed most administrator posts and visitors’ comments, and we pursued additional information through links provided on the Pages, supplementary media coverage, and available knowledge about the development of the controversy over HPV vaccination in Denmark. Using key aspects of Fairclough’s (2003) discourse analysis framework, we identified three discourses of loss, doubt, and betrayal. Associating important existential, propositional, and value assumptions affiliated with HPV vaccination, these interconnected discourses embody crucial strands of vaccination skepticism. The loss discourse emerged from personal stories about losing one’s mobility or quality of life, which then mobilized expressions of sympathy and a genuine wish that things would improve. The doubt discourse was affiliated with posts and comments questioning the evidence behind HPV vaccination. Administrators and visitors doubted information provided by the health authorities for many reasons. Some were skeptical of the epistemic value of studies showing HPV vaccination to be safe, and others simply did not trust the health authorities for sound medical advice. Finally, the betrayal discourse underlying HPV vaccination skepticism was connected to statements that accused the health authorities of betraying all those who have experienced personal loss in relation to HPV vaccination. This discourse established a difference between “us” and “them”. The “we” indicated all those afflicted by suspected adverse events, and all those taking a critical stance on HPV vaccination. The “they” were all those in favor of HPV vaccination, particularly the health authorities, pharmaceutical companies, and the Danish Cancer Society. Based on our findings, we conclude that HPV vaccination skepticism is mediated through discourses that are personal, epistemological, social or political, and value-laden in nature. Dealing with one of these dimensions alone, for example treating HPV vaccination skepticism as an information deficit or as a partisan issue, may risk missing the point entirely.